The association between intellectual capital and financial performance in the Islamic banking industry - A.A. Ousama (17075212) (2019)
Purpose The purpose of this study is to empirically investigate the impact of intellectual capital (IC) on the financial performance of Islamic banks operating in the Gulf Cooperation Council (GCC) countries. Design/methodology/approach The study measures IC by the value added intellectual coefficient model. A regression analysis was used to assess the impact of IC on financial performance. The research sample consisted of Islamic banks operating in the GCC countries during the years 2011, 2012 and 2013. Data originated from the annual reports of Islamic banks. Findings The results support the thesis that IC has a positive impact on the financial performance of Islamic banks. Even though the average IC is lower than that reported in other studies, the positive effect on financial performance is obvious. The findings also show that human capital (HC) is higher than capital employed (CE) and structural capital (SC). The study reveals that SC has an insignificant impact on the financial performance of the Islamic banks compared to CE and HC. Practical implications The findings provide empirical evidence that IC affects the Islamic banks’ financial performance. It helps Islamic banks in the GCC countries to understand how to use their IC efficiently, especially SC as it is yet to be used efficiently. Also, the findings benefit the relevant authorities (e.g. legislators and central banks) who could use them to emphasise strategic policy reforms whenever required. Originality/value The current research adds to the empirical studies in the GCC countries as it views the region as a collective as opposed to individual countries. It also extends the IC and performance measurement literature of Islamic banks in the GCC countries. Moreover, the current study enriches the limited literature on IC in the context of Islamic banking. Other Information Published in: International Journal of Islamic and Middle Eastern Finance and Management License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1108/imefm-05-2016-0073